2019
DOI: 10.3389/fsurg.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Pectoralis Plane Block for Pacemaker Insertion: A Successful Primary Anesthetic

Abstract: Effective anesthesia, analgesia, and hemodynamic stability is important to maintain during pacemaker implantation surgery, especially in the elderly population and patients with compromised cardiac function. As a strategy to avoid the need for intravenous (IV) anesthetics, peripheral nerve block techniques may be used in these specific cases. We report a case of successful pacemaker implantation surgery in a patient with severe Aortic Stenosis (AS) and Sick Sinus Syndrome (SSS) using unilateral pectoralis plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
(9 reference statements)
0
20
0
Order By: Relevance
“…Mavarez et al [22] described the use of PECS I and PECS II compartmental blocks for implantation of electronic cardiac devices (pacemakers, implantable cardioverter-defibrillators (ICDs), cardiac resynchronisation therapy (CRT) pacemakers, and others) with good results [23]. Electrodes were implanted transvenously by venipuncture of the subclavian vein or venesection of the left cephalic vein in the region of the deltopectoral groove [22]. Ince et al and Munshey et al [24] also described the successful use of PECS I and PECS II blocks for vascular access port implantation and vascular catheter implantation in children and adults [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mavarez et al [22] described the use of PECS I and PECS II compartmental blocks for implantation of electronic cardiac devices (pacemakers, implantable cardioverter-defibrillators (ICDs), cardiac resynchronisation therapy (CRT) pacemakers, and others) with good results [23]. Electrodes were implanted transvenously by venipuncture of the subclavian vein or venesection of the left cephalic vein in the region of the deltopectoral groove [22]. Ince et al and Munshey et al [24] also described the successful use of PECS I and PECS II blocks for vascular access port implantation and vascular catheter implantation in children and adults [25].…”
Section: Discussionmentioning
confidence: 99%
“…The PECS compartmental blocks were introduced into clinical practice by Rafael Blanco [20,21], mainly for perioperative analgesia in breast surgery, but over time, the use of these methods has been extended to various thoracic procedures. Mavarez et al [22] described the use of PECS I and PECS II compartmental blocks for implantation of electronic cardiac devices (pacemakers, implantable cardioverter-defibrillators (ICDs), cardiac resynchronisation therapy (CRT) pacemakers, and others) with good results [23]. Electrodes were implanted transvenously by venipuncture of the subclavian vein or venesection of the left cephalic vein in the region of the deltopectoral groove [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of muscle relaxant drugs and positive airway pressure in the intubated patient could theoretically cause an even greater hemodynamic change, deleterious to the patient with AS ( 7 ). Neuraxial anesthesia is rarely used for patients with SAS, owing to its sympathetic blockade effect that can potentially cause loss of vascular tone and cardiac output ( 8 ). Regional anesthesia, such as TPVB, is a popular technique in breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…PECS blocks had been successfully utilized for providing anesthesia for the insertion of a CRTD. Mavarez et al 38 reported the use of PECS 2 block as a sole anesthetic for pacemaker insertion in a patient with severe aortic stenosis and sick sinus syndrome. The patient required no additional intraoperative sedatives nor any postoperative opioids for 24 hours.…”
Section: Pecs Blocksmentioning
confidence: 99%
“…Kulhari et al 37 used a single bolus dose of 25 mL of ropivacaine 0.5% for PECS block. Mavarez et al 38 used a total of 20 mL of 0.5% ropivacaine with 1% lidocaine. Fujiwara et al 39 used 10 mL of 0.375% ropivacaine into the interfascial plane between pectoralis major and minor muscles.…”
Section: Pecs Blocksmentioning
confidence: 99%